Pengaruh Return On Asset Dan Debt to Equity Ratio pada Nilai Perusahaan dengan Kebijakan Deviden Sebagai Variabel Intervening - Mutia Rahmi Putri; Fitri Yeni; Agam Mei Yudha (Economic Reviews Journal, 2024)
This research investigates how Return On Assets and Debt-to-Equity Ratio influence Company Value by using dividend policy as a mediator. The focus is on manufacturing companies listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022, with a sample of 46 companies selected through purposive sampling from a population of 214. Panel data regression analysis is used for analysis. The research results show that Return on Assets has an impact on dividend policy, as does the Debt-to-Equity Ratio. Both Return on Assets and Debt-to-Equity Ratio partially influence company value, as does dividend policy. However, neither Return On Assets nor Debt-to-Equity Ratio have a significant effect on Company Value through dividend policy as a mediating variable. Furthermore, dividend policy does not mediate the relationship between Return on Assets and Debt-to-Equity Ratio on Company Value.